Chitosan magnetic nano composite adsorption material as well as preparation method and application thereof
By combining modified chitosan with nanoferrous tetraoxide, the chitosan magnetic nanocomposite adsorption material CSB@Fe3O4NPs was prepared, which solved the complexity and cost of heavy metal ion treatment in industrial wastewater, and achieved efficient and economical heavy metal adsorption effect.
Patent Information
- Application Number
- CN202510210444.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-05-02
AI Technical Summary
The prior art has problems such as complex process flow, high cost and possible secondary pollution in the process of treating heavy metal ions in industrial wastewater, and the selectivity of magnetic Fe3O4 nanoparticles is not ideal.
By combining 2-thiophene-formaldehyde modified chitosan with nanoferrous tetraoxide, a chitosan magnetic nanocomposite adsorption material CSB@Fe3O4NPs was prepared, which is used to improve the adsorption effect on heavy metal elements and the material recycling rate.
It has achieved efficient adsorption of a variety of heavy metal elements in industrial wastewater, with an adsorption rate ranging from 71.9% to 94.2%, and has overcome the problems of poor acid and alkali suitability and poor wrapping properties of traditional materials, providing reliable technical support.
Smart Images

Figure CN119909653A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of environmental nanomaterials, and in particular to a chitosan magnetic nanocomposite adsorption material and a preparation method and application thereof. Background Art
[0002] Heavy metals in wastewater are difficult to degrade, posing a serious threat to the ecological environment and human health. Therefore, research on efficient industrial wastewater treatment technology, especially heavy metal removal methods, is the key to preventing and controlling water pollution.
[0003] At present, the removal technologies of heavy metal ions in water are mainly divided into two categories: biological methods and physical and chemical methods. However, these methods generally have defects such as complex process flow, high cost and possible secondary pollution.
[0004] In contrast, adsorption method, as an emerging technology, selectively adsorbs heavy metal ions in wastewater through porous solid substances. It has the advantages of simple operation, low cost, safety and environmental protection. Therefore, it shows broad application prospects in the treatment of heavy metal ions in wastewater.
[0005] Magnetic Fe3O4 nanoparticles (Fe3O4NPs) are widely used as adsorption materials due to their large specific surface area, easy separation and recyclability, but their selectivity for heavy metal elements is not ideal. Chitosan, as a natural biopolysaccharide, has the advantages of being renewable, non-toxic, harmless and easy to degrade. It is also rich in active groups such as -OH and -NH2, which can form chelates with heavy metal ions to enhance the selective adsorption performance of heavy metal ions. Therefore, in order to better improve the adsorption effect of chitosan and heavy metal elements and the recycling rate of materials, it is planned to form a magnetic composite material by combining magnetic Fe3O4 nanoparticles with chitosan. However, the direct preparation of chitosan magnetic composite materials may have problems such as poor acid-base applicability of the material and weak encapsulation of magnetic nanoparticles and chitosan. In order to overcome the above shortcomings, it is necessary to first modify chitosan, and then use the modified chitosan to encapsulate the magnetic material to prepare a modified chitosan magnetic composite material. Based on the previous research, this work prepared a Schiff base chitosan magnetic nanocomposite CSB@Fe3O4NPs, and characterized the composite material and the reaction raw materials to verify the feasibility of the reaction. By preparing simulated water samples and adding a certain amount of composite materials, the content of nine heavy metal elements, Cr, Cu, Zn, As, Se, Ag, Cd, Sb, and Pb, was analyzed and detected by ICP-MS to explore the adsorption of the above nine different heavy metal elements, so as to optimize the optimal adsorption performance of 2-thiophene-formaldehyde cross-linked modified chitosan adsorbent material for heavy metal ions. At present, there are few relevant literature reports on the simultaneous adsorption and treatment of 9 heavy metal elements. Based on this, the material was applied to the actual industrial wastewater heavy metal element adsorption rate test, which will provide relevant data support for the adsorption treatment of heavy metal elements in industrial wastewater. Summary of the invention
[0006] The purpose of the present invention is to solve the prior art problems raised in the above background technology and to provide a chitosan magnetic nanocomposite adsorption material and a preparation method and application thereof.
[0007] The above-mentioned purpose of the present invention is achieved like this:
[0008] The solution of the present invention provides a chitosan magnetic nanocomposite adsorption material on the one hand, wherein the adsorption material is CSB@Fe3O4NPs prepared by combining 2-thiophene-formaldehyde modified chitosan and nano-ferrosoferric oxide.
[0009] Another aspect of the present invention provides a method for preparing a chitosan magnetic nanocomposite adsorption material, comprising the following steps:
[0010] Preparation of S1 and Fe3O4 magnetic nanoparticles:
[0011] Accurately weigh 11.0 g of FeCl3·6H2O and pour it into a flask, use a measuring cylinder to measure 90 mL of ethylene glycol, stir while pouring, wait until the FeCl3·6H2O solid in the flask is completely dissolved, then add 6.6 g of anhydrous sodium acetate, continue stirring until the solution becomes clear and transparent; then transfer the above solution to a reactor, seal it, place it in a vacuum drying oven, and react at 200°C for 8 hours; after the reaction is completed, wait for the reactor to cool to room temperature, separate the product with a magnet, wash it with ethanol and ultrapure water in turn, and finally, dry the product at 80°C in vacuum for 8 hours;
[0012] S2. Preparation of modified chitosan magnetic composite material:
[0013] At 25°C, accurately weigh 1g of chitosan and dissolve it in 50mL of 5% glacial acetic acid, stir magnetically until completely dissolved, then add 1mL of 2-thiophene-carboxaldehyde to the completely dissolved solution, and stir vigorously at 60°C for 7h; when the solution is cooled to room temperature, add 1g of Fe3O4 magnetic nanoparticles, stir while pouring, and react for 60min; after the reaction is completed, wash with NaOH and ultrapure water for 3-5 times, vacuum dry, and take out and weigh after the reaction.
[0014] On the other hand, the scheme of the present invention also provides the above-mentioned chitosan magnetic nanocomposite adsorption material or its use in preparing an adsorbent for multiple heavy metal elements in industrial wastewater, wherein the multiple heavy metal elements include Cr, Cu, Zn, As, Se, Ag, Cd, Sb, and Pb.
[0015] The difficulty and significance of the technical problem solved by the present invention are:
[0016] Heavy metal pollution is the main pollutant discharged from modern industrial wastewater. Adsorption method overcomes many defects of common treatment technologies and has become the preferred method for heavy metal treatment in industrial wastewater. Magnetic Fe3O4 nanoparticles (Fe3O4NPs) are widely used as adsorption materials due to their large specific surface area, easy separation, and recyclability, but their selectivity for heavy metal elements is not ideal. Chitosan is a natural biopolysaccharide with the characteristics of being renewable, non-toxic, and easily degradable. Its molecular structure contains abundant -OH and -NH2 active groups, which can form stable chelates with heavy metal ions, thereby significantly improving the selective adsorption capacity for heavy metal ions. The present invention solves the problems of poor acid-base applicability and weak encapsulation of traditional materials by compounding magnetic Fe3O4 nanoparticles with modified chitosan, significantly improving the adsorption effect and recycling rate, and providing reliable technical support for the efficient treatment of heavy metal elements in industrial wastewater.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] 1. The adsorption material of the present invention has large adsorption capacity, high efficiency, excellent separation performance and is recyclable;
[0019] 2. The material provided by the present invention has excellent adsorption performance for various heavy metal elements in industrial wastewater, and the adsorption rate ranges from 71.9% to 94.2%. The present invention provides important data support for the adsorption treatment of heavy metals in industrial wastewater;
[0020] 3. The solution of the present invention overcomes the problems of poor acid-base applicability of materials and weak encapsulation of magnetic nanoparticles and chitosan in the prior art of directly preparing chitosan magnetic composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a scanning electron microscope image of Fe3O4 NPs and CSB@Fe3O4 NPs in the embodiment of the present invention;
[0022] Figure 2 It is the infrared spectra of three materials, Fe3O4NPs, chitosan and CSB@Fe3O4NPs, in the embodiment of the present invention;
[0023] Figure 3 It is the influence of two different adsorption modes in the embodiment of the present invention;
[0024] Figure 4 It is the influence of adsorption time on adsorption effect in the embodiment of the present invention;
[0025] Figure 5 It is the effect of the amount of CSB@Fe3O4 NPs composite material on the adsorption effect in the embodiment of the present invention;
[0026] Figure 6 is the effect of pH value on adsorption effect in the embodiment of the present invention;
[0027] Figure 7 is the influence of the adsorption temperature on the adsorption effect in the embodiment of the present invention;
[0028] Figure 8 This is the effect of the initial concentration on the adsorption effect in the embodiment of the present invention. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0030] The implementation of the present invention is described in detail below in conjunction with specific embodiments.
[0031] Reference Figure 1-Figure 8The figure shows a preferred embodiment of the present invention.
[0032] Example: The embodiment of the present invention provides a chitosan magnetic nanocomposite adsorption material and a preparation method thereof and its application in the adsorption of various heavy metal elements in industrial wastewater. The material is composed of 2-thiophene-formaldehyde modified chitosan and nano-ferrous oxide (Fe3O4) composite, named CSB@Fe3O4 NPs. .
[0033] The following is a specific experiment of the implementation scheme of the present invention:
[0034] 1. Experiment
[0035] 1.1 Instruments and reagents
[0036] 7700x ICP-MS (Agilient, USA); KQ-600KDV high-efficiency CNC ultrasonic cleaner (Kunshan Ultrasonic Instrument Co., Ltd.); SEMSU8100 cold field emission scanning electron microscope-energy spectrometer (HITACHI, Japan); NicoletiS50 Fourier transform infrared spectrometer (Thermo Fisher Scientific, USA); DZF-6020 vacuum drying oven (Shanghai Boxun Medical Biological Instrument Co., Ltd.); microporous filter (Tianjin Linghang Experimental Equipment Co., Ltd.); disposable sterile syringe with needle 10mL (Anhui Hongyu Wuzhou Medical Instrument Co., Ltd.); PHS-2F pH meter (Shanghai Yidian Scientific Instrument Co., Ltd.); DF-101S thermal collector constant temperature heating magnetic stirrer (Gongyi Yuhua Instrument Co., Ltd.); 100mL hydrothermal reactor (Shanghai Changyi Instrument Co., Ltd.). Magnetic nano-ferroferric oxide (100nm), chitosan, FeCl3·6H2O, ethylene glycol, ethanol, 2-thiophene-carboxaldehyde, NaOH, anhydrous sodium acetate, HNO3, glacial acetic acid (analytical grade); experimental water is ultrapure water (18.2MΩ, 25℃), prepared by Nico ultrapure water machine; multi-element mixed standard solution (No.: GNM-M193425-2013, National Nonferrous Metals and Electronic Materials Analysis and Testing Center, 100mg / L, including nine elements: Cr, Cu, Zn, As, Se, Ag, Cd, Sb, and Pb); 3 water samples (collected from the factory water of an enterprise in Jiangxi Province).
[0037] 1.2 Preparation of Fe3O4 magnetic nanoparticles
[0038] Accurately weigh 11.0g (accurate to 0.1g) FeCl3·6H2O and pour it into a flask, use a measuring cylinder to measure 90mL of ethylene glycol, stir while pouring, wait for the FeCl3·6H2O solid in the flask to completely dissolve, then add 6.6g of anhydrous sodium acetate, and continue stirring until the solution becomes clear and transparent. Then transfer the above solution to a reactor, seal it, place it in a vacuum drying oven, and react at 200℃ for 8h. After the reaction is completed, wait for the reactor to cool to room temperature, separate the product with a magnet, wash it with ethanol and ultrapure water in turn, and finally, dry the product at 80℃ in vacuum for 8h.
[0039] 1.3 Preparation of modified chitosan magnetic composite materials
[0040] Referring to the existing method, with slight improvements: at 25°C, accurately weigh 1g chitosan and dissolve it in 50mL 5% glacial acetic acid, stir it magnetically until it is completely dissolved, then drop 1mL 2-thiophene-carboxaldehyde into the completely dissolved solution, and stir vigorously at 60°C for 7h. After the solution is cooled to room temperature, add 1g Fe3O4 magnetic nanoparticles, stir while pouring, and react for 60min. After the reaction is completed, wash it with NaOH and ultrapure water several times, vacuum dry it, and take it out and weigh it after the end.
[0041] 1.4. Preparation of standard solution
[0042] Quantitatively pipette 100 mg / L of multi-element national standard solution (No.: GNM-M193425-2013) into a 50 mL volumetric flask, prepare 20 mg / L of intermediate solution, and then prepare 0.01, 0.02, 0.05, 0.1, 0.2, 0.5, 1, 2, 5 and 10 mg / L of multi-element mixed standard series solutions in sequence. In each standard solution, add a certain amount of 0.5% (v / v) concentrated HNO3 to make the solution pH <2.
[0043] 1.5. Preparation of simulated water samples
[0044] The national standard solution GNM-M193425-2013 contains nine elements, namely Cr, Cu, Zn, As, Se, Ag, Cd, Sb and Pb, with a concentration of 100 mg / L. The above multi-element standard solution was quantitatively transferred into a 50 mL centrifuge tube, and pure water was added to prepare a series of simulated water samples with a concentration not exceeding 10 mg / L to explore the effect of the initial concentration on the adsorption effect.
[0045] 1.6 Experimental Methods
[0046] The surface morphologies of Fe3O4 NPs and CSB@Fe3O4 NPs were characterized by scanning electron microscopy, and the chemical structures of Fe3O4 NPs, chitosan and CSB@Fe3O4 NPs were characterized by infrared spectroscopy.
[0047] A series of mixed standard solutions of multi-metal elements were prepared, and the linearity, limits of detection (LODs) and limits of quantification (LOQs) of the ICP-MS method were studied.
[0048] The adsorption of heavy metal elements under different adsorption methods, adsorption material dosage, pH value, adsorption time, adsorption temperature, initial concentration and other conditions was investigated, and the adsorption rate was used as an indicator to evaluate the adsorption effect. The adsorption rate calculation formula is as follows:
[0049]
[0050] AR%: Indicates the adsorption rate of the heavy metal element.
[0051] C0: represents the concentration of the heavy metal element before adsorption, mg / L.
[0052] C1: represents the concentration of the heavy metal element after adsorption, mg / L.
[0053] 2. Results
[0054] 2.1 Structural Characterization
[0055] Fe3O4NPs and CSB@Fe3O4NPs were characterized by SEM. Figure 1 As shown in the figure, the overall shape of the self-made Fe3O4NPs is a relatively regular sphere, with some fragments on a few spheres and relatively dispersed, and the particle size is 163-211nm ( Figure 2 (shown in ab). Figure 1 The electron microscope image of the homemade magnetic nanoparticles coated with 2-thiophene-formaldehyde cross-linked chitosan derivatives is shown in c. Figure 1 It is similar to the ab figure in the figure, and the particle size is 200-205nm. Figure 1 Figure d shows an electron microscope image of commercially available 100 nm magnetic nanospheres coated with 2-thiophene-formaldehyde cross-linked chitosan derivatives. However, the spherical shape is not obvious and the fragmentation is severe, which may be related to the repeated washing with ethanol and water during the preparation of Fe3O4NPs. Therefore, homemade Fe3O4NPs were used in subsequent studies on the heavy metal adsorption performance of composite materials.
[0056] In order to further confirm the preparation and modification of Fe3O4 NPs, chitosan, and 2-thiophene-formaldehyde cross-linked chitosan derivative CSB@Fe3O4NPs, their corresponding groups were determined by infrared spectroscopy and compared (e.g. Figure 2 shown). Figure 2 Fe3O4NPs at 585cm -1 The stronger absorption peak may be the absorption peak of Fe-O, while 1655cm -1 It may be the absorption peak of -OH in the residual water, which is at 1633cm in CSB@Fe3O4NPs material. -1 There is such an absorption peak at 3400cm -1 The absorption peak may also be related to the presence of water.
[0057] Chitosan at 668 cm -1 It is the out-of-plane vibration peak of hydroxyl (OH). -1 、1074cm -1 and 1030cm -1 The main vibration mode of the peak at 899cm is the CO stretching vibration peak in chitosan. -1 These are the out-of-plane vibration peaks of the alkyl group (CH). At 1652, 1598 and 1430 cm -1 The main vibration mode of the peak is NH3 + Symmetrical and asymmetric bending vibrations. 2878cm -1 The peak at 1380cm is the CH stretching vibration peak of chitosan. -1 and 1430cm -1 The main vibration mode of the absorption peak at 3400cm is the alkyl (CH) deformation vibration peak. -1 There is a broad absorption peak around this point, which is because the amino groups of chitosan synthesized under acidic conditions are charged (basically NH3 + ). These infrared spectral features help to understand the chemical structure and properties of CSB@Fe3O4NPs, especially their behavior in acidic environments. The analysis of these vibration modes can reveal the interaction between chitosan and Fe3O4NPs, as well as the changes in the chemical state of chitosan under different environments.
[0058] In this material, 577 cm -1 There is an absorption peak of Fe-O at 1067 cm -1 With 885cm -1 An absorption peak appeared at the above results. The above results fully demonstrated that chitosan was loaded on the surface of magnetic nano-Fe3O4, that is, a magnetic chitosan composite material was prepared. The existence of thiophene and C=N group can be further confirmed by the material's adsorption capacity for heavy metals.
[0059] 2.2 Linearity and detection limit
[0060] Mixed standard solutions of 9 elements were prepared by stepwise dilution method, with concentrations of 0.01, 0.02, 0.05, 0.1, 0.2, 0.5, 1, 2, 5 and 10 mg / L, respectively. ICP-MS was used for detection. The results in Table 1 show that the concentration (x, μg / L) and the ratio of the peak area (y) in the mixed standard solutions of 9 elements have a good linear relationship in the range of 0.01 to 10 μg / L (R>0.999). The limits of detection (LODs) are 0.001845 to 0.1412 μg / L, and the limits of quantification (LOQs) are 0.006089 to 0.114 μg / L. Based on this standard curve, the quantitative calculation of the content of each element can be carried out.
[0061] Table 1 Linear equations, linear ranges, correlation coefficients, detection limits and quantification limits of standard solutions of 9 elements
[0062]
[0063] 2.3 Optimization of experimental conditions
[0064] According to the experimental results of preliminary determination and combined with the harmfulness of each element, nine elements, Cr, Cu, Zn, As, Se, Ag, Cd, Sb, and Pb, are selected. The adsorption effect of CSB@Fe3O4NPs materials on heavy metal elements under different adsorption methods, adsorption material dosage, pH value, adsorption time, adsorption temperature, and initial concentration conditions were investigated. In this experiment, Agilient's ICP-MS was used to determine the content of the above elements. The collision gas was helium, the sample solution was automatically aspirated, and the injection volume was 100μL.
[0065] 2.3.1 Analysis of the influence of material adsorption method on adsorption effect
[0066] By comparing static adsorption and ultrasonic vibration adsorption (such as Figure 3 As shown in Figure 2, it was found that the adsorption rate of Sb, Se, As, Pb and Ag was significantly improved by ultrasonic vibration adsorption, especially the adsorption rate of Sb, Se and As could reach more than 98%. Therefore, ultrasonic vibration adsorption was selected in subsequent experiments.
[0067] 2.3.2 Analysis of the influence of adsorption time on adsorption effect
[0068] like Figure 4As shown in the figure, with the increase of adsorption time, the adsorption rate of Cd and Zn increased rapidly, approaching 95% after 180 minutes; the adsorption rate of Sb, Se, and Cu reached more than 90% after 180 minutes; the adsorption rate of Pb, Cr, Ag, and As was close to 95% after 120 minutes. Taking comprehensive consideration, 120 minutes was selected as the optimal adsorption time.
[0069] 2.3.3 Effect of adsorption material dosage on adsorption effect
[0070] like Figure 5 As shown in the figure, the adsorption effect of the magnetic nanocomposite CSB@Fe3O4NPs on nine elements was investigated. The amount of magnetic nanocomposite CSB@Fe3O4NPs was 0.2-10 mg, and the adsorption rate of each element increased rapidly with the increase of the amount, and the maximum adsorption amount was reached at 10 mg. According to relevant reports in the literature, Schiff bases have a strong adsorption capacity for some heavy metal ions such as Sb 3+ The adsorption of Figure 5 It can be seen that when the amount of composite material increases, its effect on Sb 3+ The adsorption rate increased rapidly from 30% to about 90%, which further confirmed the existence of C=N groups in the material.
[0071] 2.3.4 Effect of different pH values on adsorption effect
[0072] Through detection and calculation, the adsorption amount of 9 elements by CSB@Fe3O4NPs composite materials in solutions with different pH values was obtained, and the curve of adsorption amount changing with pH value was obtained by origin plotting. Each element may have different ionic forms at different pH values. Magnetic materials may be partially dissolved in strong acids, and chitosan may affect the activity of amino or carboxyl groups at different pH values, thereby affecting its coordination ability with metal or non-metal elements. The possible reason is that when the pH value is low, the composite material shows adsorption of H + The positively charged property strengthens the repulsion between it and heavy metal ions, thereby reducing the chelating ability of some heavy metal ions with -NH2 and -OH. Figure 6 It can be seen that the adsorption rate of Sb, Se and As is more obvious when the pH value is in the range of 0 to 3; the removal effect of Pb and Ag is more obvious when the pH value is around 4; the removal effect of Cu and Cr is more obvious when the pH value is around 6, and the removal rate of these substances can reach more than 95%, while that of Cd and Zn can only reach 60%. It is expected that the pH value can be further increased to study its influence.
[0073] In summary, the present invention selects a solution acidity of pH 6. This selection is based on a comprehensive consideration of the adsorption efficiency of multiple elements, and is intended to ensure that the target pollutants can be efficiently removed in practical applications.
[0074] 2.3.5 Effect of adsorption temperature on adsorption effect
[0075] like Figure 7 As shown in the figure, the adsorption rates of nine different elements at five different temperatures, namely 10℃, 20℃, 30℃, 40℃, and 50℃, were investigated as the temperature increased. Except for 20℃, it can be found that the adsorption rates of the nine elements increase with the increase of temperature, indicating that the adsorption of these nine elements is affected by thermodynamics, and the maximum adsorption rate is reached at 20℃, which shows that the adsorption of the nine elements is not only controlled by thermodynamics, but may also be controlled by kinetics. Therefore, room temperature, namely 20℃, is taken as the adsorption temperature.
[0076] 2.3.6 Effect of initial concentration on adsorption effect
[0077] Initial concentration is also an important factor affecting the adsorption of various elements in water. The amount of composite adsorbent material was fixed at 10 mg at room temperature, and the pH value of the solution was adjusted to 6. Through experimental observation, it was found that the adsorption rate of different elements showed different trends with the change of initial concentration, such as Figure 8 As shown. During the adsorption process, Cu, Cd, and Zn showed a main trend of first increasing and then decreasing with the increase of initial concentration; the adsorption rates of Sb, Ag, and As showed a wave change, that is, first decreasing, then increasing, and then decreasing; the adsorption rates of Se, Pb, and Cr showed a wave change of first increasing, then decreasing, and then increasing. When the initial concentration exceeds 5 mg / L, the equilibrium adsorption amount increases slowly with the initial concentration, and the equilibrium adsorption amount gradually tends to equilibrium. It can be considered that the adsorbent is close to reaching the adsorption saturation state.
[0078] It can be seen that with the increase of initial concentration, the adsorption capacity of the adsorbent will go through different stages of change, from initial rapid adsorption to gradual saturation. By studying the relationship between initial concentration and adsorbent dosage, a scientific basis can be provided for the design of adsorption processes in practical applications to ensure that the ideal adsorption effect can be achieved for each element under different initial concentration conditions. Therefore, in practical applications, it is necessary to reasonably select and adjust the dosage of the adsorbent according to the initial concentration of the target element to ensure the best adsorption effect. It is recommended that the initial concentrations of Cu, Cd, and Zn be strictly controlled within 0.5 mg / L, while the initial concentrations of other elements can be relaxed to 5 mg / L. Based on the overall changes when the 9 elements are determined simultaneously, the initial concentration of each element is selected not to exceed 5 mg / L as the overall reference value, but special attention should be paid to the concentration limits of Cu, Cd, and Zn. Therefore, under the optimized conditions, the initial concentration of each heavy metal element in this experiment should not exceed 5 mg / L.
[0079] 2.4. Evaluation of adsorption effect of actual industrial wastewater
[0080] In this experiment, three industrial wastewater samples were collected from an enterprise in Jiangxi Province. The industrial wastewater was diluted (the dilution ratio was 1:5, and the initial concentration after dilution did not exceed 5 mg / L). 100 mL of the diluted solution was placed in a beaker and allowed to stand. The supernatant was placed in a 50 mL centrifuge tube and centrifuged at 4°C and 10,000 r / min for 10 min. 25 mL of the supernatant was taken for later use.
[0081] Then take the sample into a small beaker, add 10 mg of CSB@Fe3O4NPs composite material, and adjust the pH value to 6.0 with 0.5% HNO3 solution. Ultrasonic extraction was performed at room temperature for 120 minutes, and the magnetic adsorbent was quickly separated from the solution under the action of an external magnet. The water phase was filtered with a 0.45μm filter membrane and the content of each heavy metal element was analyzed by ICP-MS, and the adsorption rate was calculated. The results are shown in Table 2 below.
[0082] Table 2 Adsorption of 9 heavy metal elements in 3 water samples by CSB@Fe3O4NPs composite materials under optimized conditions
[0083]
[0084] From the adsorption of actual water samples, it can be seen that except for the adsorption rate of Cr element in water sample 3#, which is 34.4%, the other adsorption rates are all between 71.9% and 94.2%, which can fully meet the pre-treatment requirements of heavy metal adsorption in actual water samples. The reason for the low adsorption rate of Cr element in water sample 3# may be that the equilibrium adsorption amount has reached the saturated adsorption amount at room temperature, so the actual adsorption rate is only 34.4%. The adsorption of other elements is relatively ideal, but slightly lower than that of simulated water samples. The possible reason is that there may be organic matter and heavy metal complex interference in the actual water sample. When adsorbing the actual water sample, some impurities in the water sample may occupy the effective sites such as -OH, -NH2, C=N in the chitosan magnetic composite material, thereby reducing the complexation between the material and the heavy metal elements. Therefore, in order to increase the adsorption capacity, it is recommended to increase the bonding amount of the composite material and the degree of polymerization of the chitosan material to enhance the adsorption capacity.
[0085] In summary, the above implementation scheme and experiments of the present invention prove that the present invention successfully prepares a chitosan modified magnetic nanocomposite material (CSB@Fe3O4NPs) with large adsorption capacity, high efficiency, excellent separation performance and recyclability by compounding 2-thiophene-formaldehyde modified chitosan with nano-ferroferric oxide. Moreover, in the experiment, the optimal adsorption conditions of the material were determined by optimizing the experimental conditions, including ultrasonic oscillation adsorption, adsorption temperature of 20°C, pH value of 6, ultrasonic time of 120min and initial concentration not exceeding 5mg / L. The experimental results show that the material has excellent adsorption performance for a variety of heavy metal elements in actual industrial wastewater, and the adsorption rate ranges from 71.9% to 94.2%. The scheme of the present invention provides important data support for the adsorption treatment of heavy metals in industrial wastewater.
[0086] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A chitosan magnetic nanocomposite adsorption material, characterized in that: The adsorption material is CSB@Fe3O4NPs prepared by compounding 2-thiophene-formaldehyde modified chitosan and nano-ferroferric oxide.
2. The method for preparing a chitosan magnetic nanocomposite adsorption material according to claim 1, characterized in that: The following steps are involved: Preparation of S1 and Fe3O4 magnetic nanoparticles: Accurately weigh 11.0 g of FeCl3·6H2O and pour it into a flask, use a measuring cylinder to measure 90 mL of ethylene glycol, stir while pouring, wait until the FeCl3·6H2O solid in the flask is completely dissolved, then add 6.6 g of anhydrous sodium acetate, continue stirring until the solution becomes clear and transparent; then transfer the above solution to a reactor, seal it, place it in a vacuum drying oven, and react at 200°C for 8 hours; after the reaction is completed, wait for the reactor to cool to room temperature, separate the product with a magnet, wash it with ethanol and ultrapure water in turn, and finally, dry the product at 80°C in vacuum for 8 hours; S2. Preparation of modified chitosan magnetic composite material: At 25°C, accurately weigh 1g of chitosan and dissolve it in 50mL of 5% glacial acetic acid, stir magnetically until completely dissolved, then add 1mL of 2-thiophene-carboxaldehyde to the completely dissolved solution, and stir vigorously at 60°C for 7h; when the solution is cooled to room temperature, add 1g of Fe3O4 magnetic nanoparticles, stir while pouring, and react for 60min; after the reaction is completed, wash with NaOH and ultrapure water for 3-5 times, vacuum dry, and take out and weigh after the reaction.
3. Use of a chitosan magnetic nanocomposite adsorption material according to claim 1 or a preparation method according to claim 2 in preparing an adsorbent for multiple heavy metal elements in industrial wastewater, wherein the multiple heavy metal elements include Cr, Cu, Zn, As, Se, Ag, Cd, Sb, and Pb.
Citation Information
Cited By
Anti-aging packaging control pipeline and preparation method thereof
CN120863153A
Anti-aging encapsulated control line and method of making same
CN120863153B